PENERAPAN MODEL COOPERATIVE LEARNING TYPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP PADA MATERI MENGHITUNG LUAS PERMUKAAN DAN VOLUME BANGUN RUANG SISI LENGKUNG (TABUNG, KERUCUT, DAN BOLA) - Mochamad Arief Priyadi (Journal of Social Studies, Arts and Humanities (JSSAH), 2022)
THE APPLICATION OF THE JIGSAW TYPE COOPERATIVE LEARNING MODEL TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS' LEARNING OUTCOMES IN THE MATTER OF CALCULATING THE SURFACE AREA AND VOLUME OF CURVED SIDES (TUBES, CONES, AND SPHERES)This study aims to find out Cooperative Learning Type Jigsaw learning media can improve student learning outcomes about calculating surface area and volume of curved sides (tubes, cones, and spheres) in grades IX-E of Junior High School. To describe the process of improving student learning outcomes about calculating the surface area and volume of curved side spaces before and after using Cooperative Learning Type Jigsaw learning media. To measure the magnitude of the increase in student learning outcomes about calculating the surface area and volume of curved side spaces after using Cooperative Learning Type Jigsaw learning media. The results showed that using cooperative learning media type Jigsaw can be a fun variation of learning for students so that it is proven to improve student learning outcomes. Before using the Cooperative Learning Type Jigsaw learning media, the learning outcomes of students who have completed, reaching the Minimum Completeness Criteria are only 26.5% then there is an increase after using the Cooperative Learning Type Jigsaw learning media to 70.6% in cycle 1 and 100.00% in cycle 2. It was concluded that the use of Cooperative Learning Type Jigsaw learning media that was adapted to the learning material could create a pleasant learning situation so that there was an increase in student learning outcomes. Therefore, the researcher suggests that the use of Cooperative Learning Type Jigsaw learning media is socialized and used as an alternative in learning Mathematics in schools within the Bogor City Education Office.